Pengawasan Ombudsman Terhadap Kepentingan Publik Dalam Kaitannya Terhadap Negara Hukum Yang Berdasarkan Pancasila - Seri Mughni Sulubara; Amrizal Amrizal (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The Ombudsman of the Republic of Indonesia, hereinafter referred to as the Ombudsman, is a state institution that has the authority to oversee the implementation of public services both organized by state and government administrators including those organized by State-Owned Enterprises, Regional-Owned Enterprises, and State-owned Legal Entities as well as Private Bodies or individuals assigned the task of organizing certain public services, some or all of which are sourced from the state revenue and expenditure budget and / or regional revenue and expenditure budget. Public service is an activity or series of activities in order to fulfill service needs in accordance with laws and regulations for every citizen and resident for goods, services, and / or administrative services provided by public service providers. The purpose of this research is to find out the extent of the Ombudsman's role in overseeing professional public interest services. The research method used is empirical legal research. The findings of this study are the existence of public complaints about complicated public service procedures, non-transparent requirements, lack of certainty of costs to be incurred and the period of completion, the attitude of officers who are less responsive and many other service problems, thus creating a negative stigma against public service providers who are uncommunicative, unresponsive, not fast, still accept gratuities and do not provide clarity and comfort to customers. As a result, it needs to be examined further regarding the extent of supervision from the Ombudsman of the public interest in relation to the rule of law based on Pancasila.